The Innovation of MSME Culinary Marketing Strategy - Feti Fatimah (Universitas Muhammadiyah Sidoarjo, 2020)
The innovation of marketing strategy that can be done by SMES Culinary in Jember for business development needed an analysis about the business conditions. The formulation of the problems studied in this research is how to innovate marketing strategy with SWOT analysis for MSME culinary that exist in Jember. This method of research is done using a qualitative method of descriptive analysis with SWOT analysis. Results of external Internal MSMES is in the V quadrant marked Asterix (2.45; 2.6) which means having a stability/growth strategy to develop in the future, the strategy that can be applied to SMES, namely the strategy of maintaining and Maintaining, market penetration and product development. Result of the SWOT of the SMES culinary Jember has a strategy of S-O strategy that can be done in a SME that is to maintain product quality, set a cheap price as well as utilize local potentials. Based on the results of the innovations marketing strategy SMES culinary Jember namely developing the quality of existing products and adding product variants, set a cheap price to attract consumers as well as utilize local potential for example tourism and Culture.